Case-finding for depression in primary care (CAIRO): a multicentre, cross-sectional study in England - Christian Mallen; Sarah Lewis; Ram Bajpai; Carolyn Chew-Graham; Toby Helliwell; Tom Kingstone; Sarah A Lawton; Sara Muller (BMJ Open, 2025)
Objectives To examine the number of patients screening positive for depression, while self-completing an automated check-in screen prior to a general practice consultation.Design A descriptive cross-sectional study.Setting 10 general practices in the West Midlands, England. Recruitment commenced in March 2023 and concluded in June 2023.Participants All patients aged 18 years and over, self-completing an automated check-in screen for any general practice prebooked appointment, were invited to participate during a 3-week recruitment period.Primary and secondary outcome measures The number of patients screening positive for depression using the Whooley case finding research questions was the primary outcome measure. Secondary outcome measures included: demographic and (general practice level) deprivation differences in completion responses.Results 73.5% (n=3666) of patients self-completing an automated check-in screen participated in the CAse-fInding foR depressiOn in primary care (CAIRO) study, (61.1% (n=2239) female, mean age 55.0 years (18–96 years, SD=18.5)).28.3% (n=1039) of participants provided a positive response to at least one of the two Whooley research questions (31.2% female and 23.8% male). Significantly more positive responses were obtained from females, those aged between 35 years and 49 years and those from more deprived practices.Conclusions Over a quarter of CAIRO participants provided a positive response to at least one of the two Whooley questions, suggesting possible unmet need in the population studied. A follow-up study could investigate whether responses provided at the point of check-in are raised and addressed in the subsequent consultation.